2001
DOI: 10.1074/jbc.m007231200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-ζ Phosphorylates Insulin Receptor Substrate-1 and Impairs Its Ability to Activate Phosphatidylinositol 3-Kinase in Response to Insulin

Abstract: Protein kinase C-(PKC-) is a serine/threonine kinase downstream from phosphatidylinositol 3-kinase in insulin signaling pathways. However, specific substrates for PKC-that participate in the biological actions of insulin have not been reported. In the present study, we identified insulin receptor substrate-1 (IRS-1) as a novel substrate for PKC-. Under in vitro conditions, wild-type PKC-(but not kinase-deficient mutant PKC-) significantly phosphorylated IRS-1. This phosphorylation was reversed by treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
159
2
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(171 citation statements)
references
References 45 publications
(65 reference statements)
7
159
2
2
Order By: Relevance
“…Expression of PKCz seems to be regulated by LC-CoA in insulin secretion stimulated by palmitate (Yaney et al, 2000). The isoform PKCz is also activated by insulin and mediates the phosphorylation of IRS proteins (Liu et al, 2001;Ravichandran et al, 2001). As a consequence the IR-IRS complexe dissociates, inhibiting the ability of IRS proteins to induce tyrosine phosphorylation (Liu et al, 2001).…”
Section: Insulin Receptor In Pancreatic B-cellmentioning
confidence: 99%
“…Expression of PKCz seems to be regulated by LC-CoA in insulin secretion stimulated by palmitate (Yaney et al, 2000). The isoform PKCz is also activated by insulin and mediates the phosphorylation of IRS proteins (Liu et al, 2001;Ravichandran et al, 2001). As a consequence the IR-IRS complexe dissociates, inhibiting the ability of IRS proteins to induce tyrosine phosphorylation (Liu et al, 2001).…”
Section: Insulin Receptor In Pancreatic B-cellmentioning
confidence: 99%
“…Insulin receptor substrate-1 (IRS-1), one major intracellular substrate of the insulin receptor kinase, interacts with the insulin receptor at sites adjacent to the N-terminus. Recently it was found that during insulin signaling IRS-1 is phosphorylated by protein kinase C (PKC)-, thereby attenuating the insulin signal transduction [2,3]. To disclose these phosphorylation sites, we developed a mass spectrometric strategy combining two independent MS methods.…”
mentioning
confidence: 99%
“…In fact, atypical PKCs are essential for insulin stimulation of glucose transport in muscle tissue [41]. Although atypical PKCs are located downstream of IRS-1 and PI3-kinase in insulin signalling, IRS-1 is also a novel substrate for atypical PKCs [42]. Moreover, suppressors of cytokine signalling (SOCS) proteins have been implicated in the insulin signalling network [43].…”
Section: Discussionmentioning
confidence: 99%